The Effect of Information Technology on Retailer Satisfaction Through Supply Chain Management Practices and Retailer-Distributor Relationship in Modern Retailer Surabaya - Jiputra, Juan Alexander; Tarigan, Zeplin Jiwa Husada; Siagian, Hotlan (Master of Management Study Program, Faculty of Business and Economics - Petra Christian University, 2020)
Supply chain management is vital for manufacturing companies in connecting suppliers, manufacturers, distributors, and corporate customers. The company's products will enter the company's distribution system through distributors, retailers, and end customers. This study examines how to enhance retailer satisfaction by taking into account the application of information technology, supply chain management practices, and retailer-distributor relationships. This study surveyed 86 modern retailers using a five-point Likert scale questionnaire. Data processing used PLS. The results showed that the information technology significantly improves the retailer-distributor relationships with a coefficient of 0.303. Also, information technology affects supply chain management practices with a coefficient of 0.527. Information technology has an effect of 0.281 on retailer satisfaction. The company implementing supply chain management practice improves the retailer-distributor relationship by 0.518, and supply chain management practice affects retailer satisfaction by 0.291. The results also showed that the retailer-distributor relationship affects retailer satisfaction by 0.358. This research provides an insight for the practitioner on how to improve the retailer satisfaction. This paper also contributes to the ongoing research in the field of supply chain management.